Entrepreneurial new venture skills - Lussier, Robert N.; Kimball, David Charles 1959-; Corman, Joel (Routledge, 2015)
Focusing on the entrepreneurial start-up process, the third edition of Entrepreneurial New Venture Skills nbsp;takes the reader through the steps of selecting, planning, financing, and controlling the new venture. The authors cover multiple forms of new ventures, as well as ways to utilize entrepreneurial skills in other contexts, encouraging students to engage with the material and apply it to their lives in ways that make sense for them